Virulence of monosporic isolates of Isaria fumosorosea on immatures of Bemisia tabaci - Ruiz Sánchez, Esaú; Chan Cupul, Wilberth; Cristóbal Alejo, Jairo; Tun Suárezq, José María; Pérez Gutiérrez, Alfonzo; Lara Reyna, Joel (Revista Mexicana de Ciencias Agrícolas, 2018)
Entomopathogenic fungi are a promising alternative for the biological control of insect pests in agriculture. In this study, we evaluated the virulence of eight monosporic isolatesnativetoYucatan,usingasareferenceamonosporic isolate from a commercial strain of Isaria fumosorosea on eggs and nymphs of Bemisia tabaci. The dose-mortality bioassays were performed with four spore suspensions (1 x 104 to 1 x 107 conidia ml-1). We evaluated the mortality of eggs and nymphs and calculated the LC50 and LT50 for all isolates. Egg mortality at 7 days after inoculation of 1 x 107 conidia ml-1 ranged between 28.6 and 59.1%; the native monosporic isolates If-Hal M1 and If Tim M1 were the most virulent, causing 59.1 and 51.1% mortality, respectively. The mortality of the nymphs 12 days after inoculation of 1 x 107 conidia ml-1 ranged between 59.6 and 81%; the native monosporic isolates If-If-Tiz M1 and If-Hal M1 obtained the highest values with 81 and 70.5%, respectively. The median lethal concentration (LC50) was lower for the monosporic isolate of the commercial strain Pae-sin M1 with 1.4 x 105 conidia ml-1. Regarding mean lethal times (LT50), it was observed that the lowest ones were those of the monosporic isolate of the commercial strain Pae-sin M1 and of the native isolate If-Hal-M1 with 4.9 and 5 days, respectively. Two native monosporic isolates (If-Tim-M1 and If-Hal-M1) showed high enough virulence to be considered for a regional bio-pesticides production program in the Yucatan Peninsula.
Keywords: biological control; entomopathogenic fungus; white f ly